Mixed iodonium-, phosphonium-, arsonium-, sulfoniumdiazonium ylides in reactions with nucleophiles - Podrugina, Tatyana A.; Pavlova, A. S.; Vinogradov, D. S.; Shuvalov, M. V.; Potapov, I. D.; Levina, I. I.; Mironov, A. V.; Gleiter, Rolf (Russian chemical bulletin, 2019)
The reactions of mixed ylides containing a diazonium fragment and an "onium" group of different nature with nucleophiles were studied. In the iodonium-diazonium and sulfoniumdiazonium ylide, the nucleophile first of all substitutes the iodonium and sulfonium group. A series of hetaryl-substituted phosphazines was obtained by a one-pot process of nucleophilic substitution in a diazonium-iodonium ylide with subsequent nucleophilic addition of triarylphosphine at the diazo group.